Clinical applicability of short form of Bruininks-Oseretsky Test of Motor Proficiency Second Edition in patients after treatment of acute lymphoblastic leukemia - Šnajdrová, Tereza; Patrmanová, Eliška; Jevič, Filip; Bořilová, Karolína; Hrdoušková, Monika; Musálek, Martin (Frontiers in Pediatrics, 2023)
Introduction Acute lymphoblastic leukaemia (ALL) ranks among paediatrics' most common oncological malignancies. Monitoring motor performance levels associated with self-sufficiency in the everyday activities of ALL patients is extremely important during treatment. The motor development of children and adolescents with ALL is most often assessed using the Bruininks-Oseretsky Test of Motor Proficiency Second Edition (BOT-2) complete form (CF) with 53 items or the short form (SF) with 14 items. However, there is no evidence in research that BOT-2 CF and SF give comparable results in the population of patients with ALL. Objective This study aimed to determine the compatibility of motor proficiency levels achieved from BOT-2 SF and BOT-2 CF in ALL survivors. Materials and Method The research sample consists of n = 37 participants (18 girls, 19 boys) aged 4–21 years (10.26, ± SD 3.9) after treatment for ALL. All participants passed BOT-2 CF and were at least 6 months and a maximum of 6 years from the last dose of vincristine (VCR). We used ANOVA with repeated measures, considering the sex, intra-class correlation (ICC) for uniformity between BOT-2 SF and BOT-2 CF scores and Receiving Operating Characteristic. Results BOT-2 SF and BOT-2 CF assess the same underlying construct, and BOT-2 SF and CF standard scores have good uniformity: ICC = 0.78 for boys and ICC = 0.76 for girls. However, results from ANOVA showed that the participants achieved a significantly lower standard score in SF (45.1 ± 7.9) compared to CF (49.1 ± 9.4) (p < 0.001; Hays ω2 = 0.41). ALL patients performed the worst in Strength and Agility. According to the ROC analysis, BOT-2 SF obtains acceptable sensitivity (72.3%) and high specificity (91.9%) with high accuracy of 86.1%, and the fair value of the Area Under the Curve (AUC) = 0.734 CI95% (0.47–0.88) in comparison to BOT-2 CF. Conclusions To reduce the burden on ALL patients and their families, we recommend using BOT-2 SF instead of BOT-2 CF as a useful screening tool. BOT-SF can replicate motor proficiency with as high probability as BOT-2 CF but systematically underestimates motor proficiency.